Andrik Sulistiyawan Sukarno and the Managerial State of Indonesia - Sulistiyawan, Andrik (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The book, Authoritarian Modernization in Indonesia’s Early Independence Period: The Foundation of the New Order State, 1950-1965, is a remake of the author’s PhD dissertation in Leiden University in the Netherlands, and, it consists of seven chapters and three major discussion parts i.e., 1) elite ideology and formation, 2) the development of institutions and the importation of ideas and ideologies during the 1950s, 3) the development of both national planning and scientific management within the context of the Guided Democracy.